Damage control orthopaedics is associated with impaired fracture healing and delayed recovery in a rodent model of severe multiple trauma - Changlin Qi; Nils Becker; Nan Zhou; Diana Möckel; Twan Lammers; Rebecca Halbgebauer; Johannes Greven; Maximilian Praster; Frank Hildebrand; Klemens Horst; Elizabeth R. Balmayor (Bone & Joint Research)
Aims: Polytraumatized patients with severe limb injuries often develop complications, which are influenced by the surgical treatment strategy. For the initial fracture stabilization, Early Total Care (ETC) and Damage Control Orthopedics (DCO) are competing concepts, with the treatment choice depending on the patient’s condition. Clear guidance factors remain lacking. Our study aimed to compare the effects of ETC and DCO strategies on fracture healing and functional gait behaviour in a rat multiple-trauma model. Methods: A standardized rat multiple-trauma model was established, which included haemorrhagic shock, blunt chest trauma, and a femur fracture with subsequent reduction and fixation by group-specific operative strategies. Adult Sprague-Dawley male rats (n = 45) were randomly allocated to three groups: Sham (n = 9), ETC (primary intramedullary nailing (IN); n = 18), and DCO-IN (external fixation with conversion to IN at day 6 after the trauma; n = 18). Postoperative gait changes at different timepoints were analyzed using the CatWalk system. At seven, 21, and 42 days, the animals were euthanized to assess bone formation of the femur fracture histologically and via micro-CT. Biomechanical stability was assessed by a three-point bending test. Results: Fixation conversion surgery in the DCO-IN group decreased callus formation, resulting in delayed fracture healing with reduced callus quality and poorer biomechanical properties compared to the ETC group. The DCO-IN group also exhibited poorer weightbearing and locomotor-function rehabilitation compared to the ETC group, consistent with the impaired fracture healing process. Conclusion: These results demonstrate that conversion of the fixation method in the DCO strategy delays the callus formation process up to six weeks after trauma, potentially contributing to delayed rehabilitation and higher risk of nonunion in multiple-trauma patients. DCO should be limited to patients with contraindications for ETC, underlining the need for clear identification factors. Cite this article: Bone Joint Res 2025;14(7):619–632.